Mechanical behaviour of austenitic stainless steel loaded in the aqueous solution of H2SO4 during tensile testing - Abboub, Amar; Aboura, Ahmed; Benmahdi, Khaled; Sadoun, Mohamed; Belkacem, Mokhtar; Semsoum, Djameleddine (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Stainless steels have excellent corrosion resistance and adequate mechanical properties. However, their use in aggressively hydrogenated environments in the energy industry causes a loss of ductility. This work studied the effect of hydrogen on the mechanical behavior of the DINX15CrNiSi25.21/AISI310 austenitic stainless steel loaded in an aqueous solution of purely sulfuric acid H2SO4 at 1N at room temperature during tensile testing.Methods: Experimental characterization techniques are applied to standardised machining-manufactured tensile specimens which underwent a series of heat treatments ranging from quenching at 1050°C for 35 minutes to tempering at 680°C for 30 minutes. This is accompanied by a succession of immersions of these samples by cryogenic quenching cycles at -196°C for a duration of 1 hour. The hydrogen was electrolytically loaded in a Pyrex glass cell for various loading times, ranging from 1h00 to 15h00, with a step of 2h00.Results: The results showed a reduction in mechanical properties and plasticity. The electrochemical method confirmed the material's sensitivity to hydrogen embrittlement, calculating the embrittlement criterion EI (%). This method indicates a rapid increase in values depending on hydrogen loading times, with a maximum value of 41.60%.Conclusion: The study highlights the negative impact of hydrogen on the mechanical properties of  AISI310 stainless steel, emphasising the need for reduced hydrogen exposure in steel applications.
Keywords: austenitic stainless steel; heat treatments; hydrogen pre-loaded; mechanical properties; hydrogen embrittlement (HE); faces